Think Piece on Green Guerrilla: Creating Sustainable Development through Sustainability Bildung - Sofiya Henrietta Angelina Olsen (Environmental Association of Southern Africa, 2018)
By drawing on a 12-week anthropological fieldwork study, I explore how education for sustainable development is perceived and practised in the Danish folk high school course Green Guerrilla. Through the emic approach of sustainability Bildung I argue that the Green Guerrilla course constitutes a radical political imaginary; a space where the students learn to train their sociological imagination and reflect upon themselves and their own culture and society from an outside perspective in order to imagine how it can be structured differently. I argue that during a five-day study trip to a Swedish forest, the students learn to be in and actively engage with nature through the senses, and experience how they are inextricably connected with their environment. They learn that creating a sustainable world means 'dealing with your own shit', in more ways than one. Through this sustainability Bildung the students learn that it is up to them to 'find their own forest' - that is, to figure out how they can create the lives that they want to live in the future.